Practical Chain‐End Reduction of Polymers Obtained with ATRP. Issue 18 (18th May 2017) - Gutekunst, Will R.; Anastasaki, Athina; Lunn, David J.; Truong, Nghia P.; Whitfield, Richard; Jones, Glen R.; Treat, Nicolas J.; Abdilla, Allison; Barton, Bryan E.; Clark, Paul G.; Haddleton, David M.; Davis, Thomas P.; et al.
Abstract : A mild, robust, and clean reduction of atom transfer radical polymerization chain‐ends. Using a combination of catalytic palladium‐on‐carbon and hydrogen gas, a straightforward method for the hydrogenolysis of halide‐terminated polymers is reported. This method is effective on several monomer classes (acrylate, stryrene, methacrylate) and performs excellently in numerous solvents. Abstract : A practical and user‐friendly strategy for the chain‐end reduction of halogen terminated polymers that employs hydrogen gas and heterogeneous catalysis (palladium on carbon) is reported. Quantitative dehalogenation of a wide variety of monomer families (polystyrenes, polyacrylates, and polymethacrylates) with either chlorine or bromine chain‐ends is observed. The utility of this chain‐end reduction is further highlighted by mild reaction conditions, simple purification, and compatibility with a wide range of solvents.